Memaknai Akun Media Sosial Satire Kristen dalam Perspektif Etis-Teologis - Olimbovo, Senopati Salomo; Novalina, Martina (STT Iman Jakarta, 2023)
This research is motivated by several irregularities that often occur in the church. This problem results in harmony in the church; for example, the relationship between the congregation and the Pastor becomes tenuous due to irregular teaching. Satire is valuable to satirize someone so that the person being ridiculed makes improvements and thinks more broadly. You can often find satirical sentences on social media accounts, both satire and sarcasm. But this time, many social media accounts are displaying satirical language-style forms of satire about the church, both in terms of order and teachings in the church. This article raises issues that exist on the social media account @gerejapalsu. This account can be a consideration regarding Pastors who are considered to emphasize their physical appearance rather than the truth of the Word that will be conveyed and teachings that are